Lonely children and adolescents are less healthy and report less social support: A study on the effect of loneliness on mental health and the moderating role of social support - Raphael Schütz; Franziska Reiss; Irene Moor; Anne Kaman; Ludwig Bilz; HBSC Study Group Germany (BMC Public Health)
Abstract Background Loneliness among children and adolescents has been increasingly recognized as a public health issue, for example, because of its associations with mental health problems. Nevertheless, there is a lack of evidence regarding the links between loneliness and mental health and the potential buffering role of social support. Thus, this study aims to investigate the prevalence of loneliness among children and adolescents in Germany and its associations with mental health. Furthermore, we analyze whether social support is negatively correlated with loneliness and mental health problems and whether it acts as a moderator of the association between loneliness and mental health issues. Methods This study analyzed data from the Health Behavior in School-aged Children (HBSC) survey in Germany in 2022, which included 6,475 students aged 11, 13, and 15 years (girls: 50,6%, M age = 13,4, SD = 1,7). Loneliness was measured via the University of California–Los Angeles Scale (UCLA) and a single-item measure. The mental health indicators included subjective health, life satisfaction, and multiple psychosomatic complaints. Social support from family, teachers, and classmates was assessed. Chi-square tests, t tests, logistic regressions, and moderation analyses were conducted. Results A total of 17.2% of the students reported high levels of loneliness. Compared with boys, girls and gender-diverse students reported higher rates of loneliness. High levels of loneliness were strongly linked to poorer subjective health (OR = 5.56, p <.001), lower life satisfaction (OR = 7.32, p <.001), and increased psychosomatic complaints (OR = 7.38, p <.001). High social support from family, teachers, and students was associated with reduced loneliness and better mental health outcomes. Teacher support in grades 7 and 9 buffered the effect of loneliness on multiple psychosomatic complaints. Conclusion The findings highlight that loneliness is a prevalent phenomenon among children and adolescents and is strongly associated with mental health issues. Greater social support is linked to reduced loneliness and better mental health, so targeted interventions to promote social support in schools and families are needed to address loneliness. Future research should explore longitudinal relationships and further elucidate the mechanisms underlying these associations.